A Letter to Naomi Klein - Webb, Mark (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
Dear Naomi Klein, I recently finished reading your latest book, The Shock Doctrine. Your detailed account of the connections between neoliberal economic policy and the use of violent repression, the decline of welfare states, and the rise of corporatized war and disaster capitalism is compelling.